2001
DOI: 10.5694/j.1326-5377.2001.tb143245.x
|View full text |Cite
|
Sign up to set email alerts
|

Firecracker injuries to the hand

Abstract: Between September 1999 and April 2000, the Hand Unit at St George Hospital, Sydney, treated three young men with severe injuries caused by holding a lighted firecracker, These cases illustrate the typical injuries seen with this mechanism of injury. They highlight the dangers of these explosive devices and the potential to improve the laws relating to fireworks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In reviewing the literature, we have observed a trend toward increased reporting of severe firework hand injuries and believe that this may be due to a combination of improved awareness and diagnosis, 11 as well as greater access by members of the public to fireworks of increasing power. 12 Previously, MacKenzie et al described a predisposition to radial-side soft tissue injuries of the thenar eminence and first web space loss 13 while Hahn et al suggested further bony involvement of either the thenar or hypothenar rays while sparing those located centrally. 14 Philipson and Southern then described propagation of the blast proximally, which resulted in acute carpal tunnel syndrome, median nerve contusion, and devitalization of forearm muscles.…”
Section: Type Iii-carpometacarpal Joint Dislocations + Axial Carpal Dmentioning
confidence: 99%
“…In reviewing the literature, we have observed a trend toward increased reporting of severe firework hand injuries and believe that this may be due to a combination of improved awareness and diagnosis, 11 as well as greater access by members of the public to fireworks of increasing power. 12 Previously, MacKenzie et al described a predisposition to radial-side soft tissue injuries of the thenar eminence and first web space loss 13 while Hahn et al suggested further bony involvement of either the thenar or hypothenar rays while sparing those located centrally. 14 Philipson and Southern then described propagation of the blast proximally, which resulted in acute carpal tunnel syndrome, median nerve contusion, and devitalization of forearm muscles.…”
Section: Type Iii-carpometacarpal Joint Dislocations + Axial Carpal Dmentioning
confidence: 99%
“…Most of these injuries are to fingers and are the result of a diverse array of causes including fireworks, slammed doors, exercise bicycles, farm equipment, and shop class. [4][5][6]9,11,12,22,24,25,27,28 Replantation and revascularization can be successful in this patient population compared with adults as described in several case series. 1,3,7,26,30,35 The incidence, temporal trends, and patient characteristics of upper extremity traumatic amputations in children are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, serious hand injuries have been reported in association with the explosion of hand-held crackers that were purchased in the ACT and brought into NSW for use. 4 Disappointingly, the data used here also contained only very limited information on the place that injuries occurred, and the activity that victims were engaged in at the time of injury. Although the ICD-10-AM coding system theoretically enables capture of this information in the external cause code for injuries, it is only rarely recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Important strategies for reduction of firework injuries include national harmonisation of regulations regarding sale and use of fireworks, active enforcement of these regulations, and increasing community awareness of the degree of risk associated with illegal fireworks. 3,4 Improved recording of firework injuries in hospital data, including information regarding the type of firework involved, and the circumstances of the injury, could provide a stronger information base on which to build and monitor prevention strategies in NSW.…”
Section: Discussionmentioning
confidence: 99%